Peran Guru dalam Membentuk Moral Anak di TPQ Bani Adnan Wonocolo Surabaya - taseman taseman; Iman Rasiman; Amilya Nurul Erindha; Inayatur Rofi’ah (JIEES : Journal of Islamic Education at Elementary School, 2021)
Moral is the ability to determine good and bad behavior that must be owned by everyone, including children. Al-Quran Education Park (TPQ) Bani Adnan is a non-formal educational institution that organizes Qur'an education and moral teaching in the Jemurwonoari village, Wonocolo District, Surabaya. The purpose of this study was to determine the role of the teacher, the obstacles experienced, and the solutions made in teaching morals to children at TPQ Bani Adnan. This research is a descriptive qualitative research. The data collection technique used was by conducting interviews with the chairman of the Bani Adnan TPQ and direct observation of teaching and learning activities carried out at the Adnan Bani TPQ. The findings of this study indicate that moral teaching at TPQ Bani Adnan through daily activities, namely praying before and after learning, memorizing short letters, reciting volumes with the Tilawati method, and providing examples of daily morals. The obstacles experienced by teachers in teaching morals to children are the diversity of characteristics in children. Moral teaching is carried out continuously so that children can get used to it and apply it in everyday life. The role of the TPQ teacher is very important in the formation of morals in children, namely through the teacher's ability to understand the characteristics of children and provide real examples.